Transulnar access for coronary intervention in a 23‐year‐old with accelerated coronary atherosclerosis due to congenital aortic hypoplasia - Jonathan D. Dawkins; Ari M. Cedars; Jeffrey M. Schussler (Clinical Case Reports, 2019)
Key Clinical Message The use of alternative arterial access and advanced imaging is not only applicable to mainstream adult cardiology, but helpful and sometimes necessary in taking care of adult patients with complex congenital heart disease.